1997
DOI: 10.1074/jbc.272.6.3694
|View full text |Cite
|
Sign up to set email alerts
|

The Glucocorticoid-responsive Gene Cascade

Abstract: The gene for liver-type arginase, an ornithine cycle enzyme, is induced by glucocorticoids in a delayed secondary manner. An enhancer element located around intron 7 of the rat arginase gene shows delayed glucocorticoid responsiveness, and it harbors two sites binding with members of the CCAAT/enhancer binding protein (C/EBP) family. Here, we investigate the role of these C/EBP binding sites in glucocorticoid response of the arginase gene. When inserted in front of the herpes simplex virus thymidine kinase pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…This conclusion does not rule out the possibility that de novo synthesis of a factor(s) is necessary to realize a full response. The expression of C/EBP␣ and -␤ is, for example, rapidly induced by glucocorticoids and cAMP and is involved in the hormone-induced expression of several genes (9,10,20,39,50). A crucial role for members of the C/EBP family of transcription factors in achieving the full response of the GRU fits with our observation that the C/EBP site within the GRU is essential for the function of the unit and, hence, for the activation by glucocorticoids.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This conclusion does not rule out the possibility that de novo synthesis of a factor(s) is necessary to realize a full response. The expression of C/EBP␣ and -␤ is, for example, rapidly induced by glucocorticoids and cAMP and is involved in the hormone-induced expression of several genes (9,10,20,39,50). A crucial role for members of the C/EBP family of transcription factors in achieving the full response of the GRU fits with our observation that the C/EBP site within the GRU is essential for the function of the unit and, hence, for the activation by glucocorticoids.…”
Section: Discussionsupporting
confidence: 65%
“…The glucocorticoid-induced activation of the CPS enhancer fragment that lacks the GRE (Fig. 4, construct 4), on the other hand, may well be indirect and reflect glucocorticoidinduced expression of transcription factors such as C/EBP (9,20), for which binding sites are present in the CRE-containing fragment.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings of a dramatic fall in the expression of CPS and arginase genes in the livers of C/EBP␣-deficient mice are consistent with these previous observations and underline the importance of C/EBP␣ in the regulation of the expression of these two genes. However, our previous studies have shown that C/EBP␤ rather than C/EBP␣ activates the arginase promoter more strongly (12) and is more crucial for stimulation of the arginase enhancer in response to glucocorticoids (13,40). Thus, it is likely that C/EBP␣ is involved in basal level expression of the gene, whereas C/EBP␤ is important for high level expression of the arginase gene induced by glucocorticoids in response to dietary changes, etc.…”
Section: Discussionmentioning
confidence: 94%
“…Sucraseisomaltase may represent a secondary response gene because its induction by steroids is delayed (22). Steroids are capable of inducing the synthesis of several transcription factors, including C/EBP-␣, C/EBP-␤, C/EBP-␥, and IB, which in turn may influence the downstream expression of a group of secondary response genes (7,12). Although both C/EBP-␤ and C/EBP-␥ mRNA transcripts have been detected in the intestine, only C/EBP-␣ has been identified immunohistochemically in terminally differentiated cells of the villus (28).…”
Section: Discussionmentioning
confidence: 99%